NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis

Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.

N-heterocyclic carbene-catalyzed atroposelective synthesis of N-N axially chiral 3-amino quinazolinones - Balanna, Kuruva; Barik, Soumen; Barik, Shilpa; Shee, Sayan; Manoj, Niket; Gonnade, Rajesh G.; Biju, Akkattu T. (ACS Catalysis, 2023)
Although the atroposelective synthesisof biaryls and related compoundsbearing axially chiral C-C bonds is well-known, the synthesisof axially chiral C-N bond-containing compounds is relativelyless explored, and the construction of axially chiral N-N bondshas received only scant attention. Demonstrated herein is the N-heterocycliccarbene (NHC)-catalyzed selective amidation reaction, leading to theatroposelective synthesis of N-N axially chiral 3-amino quinazolinones.The NHC-catalyzed reaction of quinazolinones containing a free N-Hmoiety with & alpha;,& beta;-unsaturated aldehydes under oxidativeconditions furnished the atropisomeric quinazolinone derivatives undermild conditions and broad scope. Preliminary studies on experimentaland density functional theory-based N-N rotational barrierdetermination are also presented.
Keywords: amino quinazolinones; asymmetriccatalysis; axial chirality; N-heterocycliccarbenes; organocatalysis